Oxytocin microinjected into the central amygdaloid nuclei exerts anti-aggressive effects in male rats. (March 2015) - Calcagnoli, Federica; Stubbendorff, Christine; Meyer, Neele; de Boer, Sietse F.; Althaus, Monika; Koolhaas, Jaap M.
Abstract: We recently demonstrated that acute and chronic intracerebroventricular enhancement of brain OXT levels induces potent anti-aggressive and pro-social explorative effects during social challenges. However, the exact anatomical location in the brain where OXT exerts its action is still elusive. In the present study, we targeted two critical brain areas, i.e. the central amygdala (CeA) and the dorsal raphe (DR), both containing high levels of OXT receptors (OXTRs) and constituting important nodes of the neural circuitry related to aggression. Behavioral effects of local micro-infusion of OXT and OXTR antagonist, L368.899, (alone and combined) were evaluated in resident male rats during confrontations with an unfamiliar male intruder. Our results show that OXT microinjected into the CeA markedly reduced resident's offensive behavior and facilitated social exploration, without affecting other non-aggressive behaviors. The receptor specificity of the behavioral effects was verified when a micro-infusion of a selective OXTR antagonist nullified the changes. Pharmacological blockade of CeA OXTRs per se was without clear behavioral effects suggesting that endogenous OXT within the CeA does not play a major inhibitory role on offensiveness. Anatomical specificity was also supported by the absence of relevant behavioral effects when OXT was microinjected into more medial sub-regions of the amygdala. Likewise, within the DR neither OXT nor OXTR exerted significant effects on offensive aggression, while microinjection of the 5-HT1A autoreceptor agonist in this region significantly suppressed aggression. In conclusion, our results point at the CeA as an important brain site of action for the anti-aggressive and pro-social explorative effects induced by exogenous enhancement of brain OXT levels. Highlights: OXTergic manipulation of the CeA of rats induces socio-behavioral changes. OXT infusion into the CeA reduces attack duration towards a male intruder. OXT infusion into the CeA increases social exploration. OXT-induced effects are selectively mediated by OXT receptors.